АНАЛІЗ ПЕРЕХІДНИХ ПРОЦЕСІВ ПРИ ПОСТАНОВЦІ ЛЕП ЗМІННОГО СТРУМУ ПІД НАПРУГУ В ГІБРИДНИХ ЕНЕРГОСИСТЕМАХ - Шполянський, О.Г. (Інститут електродинаміки НАН України, Київ, 2022)
The paper analyses the transients that occur during the energisation of overhead transmission line 750 kV in a hybrid power system. It is shown that the power supply of the AC transmission line from the high voltage direct current transmission allows using converter control system to limit the switching overvoltage and the aperiodic currents. This enriches the list of traditional measures to improve the safety of AC power systems. References 8, tables 2, figures 1.